THE CIVIL LEGAL NATURE OF LIMITED MATERIAL RIGHTS (World Bulletin of Management and Law, 2022)
The article examines the problematic issues of determining the legal nature of limited material rights, and analyzes the signs of limited material rights established by national civil legislation and formed by scientists in the doctrine of civil law. On the basis of the performed analysis, it is proposed to determine the limited material right by its characteristics characteristic of all its types
Keywords: property rights; limited material rights; servitude; superficies